ANALISIS PERAN MASYARAKAT DALAM MENCIPTAKAN EXCELLENT HOSPITALITY DI KAMPUNG INGGRIS PARE - Muhammad Aqil Haibatul Akbar; Elly Malihah; Rini Andari (Media Bina Ilmiah, 2023)
The English village of Pare is now widely known by many people as a tourist spot that offers unique tourist attractions to attract tourists to visit the English village. The tourist attraction shown by Kampung Inggris is learning English with the habituation method to communicate using English. The development of a tourist destination, especially in the English village of Pare, is one of the efforts of a destination to maintain a tourist attraction so that it remains attractive so that tourists are still interested in visiting the English village of Pare. In an effort to maintain this attraction so that tourists continue to be interested in traveling to English village Pare and feel satisfied, managers in English village Pare need a way to maintain this attraction. Good service or excellent service for tourists is currently still considered a good solution for managers of tourist destinations in meeting the needs and desires of customers or tourists (Hermawan, 2020). This is the reason for conducting research in the English village of Pare by analyzing the role of the community in creating excellent service or excellent hospitality in the English village of Pare using the theory of service quality dimensions.